2012
DOI: 10.1186/1476-069x-11-79
|View full text |Cite
|
Sign up to set email alerts
|

Association between bisphenol A exposure and body mass index in Chinese school children: a cross-sectional study

Abstract: BackgroundThere is increasing evidence suggesting that Bisphenol A (BPA), one of the highest volume chemicals produced worldwide, can interfere with the body’s natural weight control mechanisms to promote obesity. However, epidemiological studies for this are limited, especially for children.MethodsA cross-sectional study was conducted to investigate the association between BPA exposure and body mass index (BMI) in school children. Three primary and three middle schools were randomly selected from 26 primary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 50 publications
8
83
0
Order By: Relevance
“…Similar results were seen in other crosssectional studies where older children had higher BPA concentrations that correlated to an increased risk of being overweight/ obese, specifically in females. 142,143 A cross-sectional study examining NHANES data (2003)(2004)(2005)(2006)(2007)(2008) found that urinary BPA concentrations were significantly associated with obesity in children and adolescents after controlling for several cofactors. 6 Another study using the NHANES data reported that non-Hispanic white boys were more likely to be overweight/obese, independent of other major risk factors, as a result of exposure to BPA.…”
Section: Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were seen in other crosssectional studies where older children had higher BPA concentrations that correlated to an increased risk of being overweight/ obese, specifically in females. 142,143 A cross-sectional study examining NHANES data (2003)(2004)(2005)(2006)(2007)(2008) found that urinary BPA concentrations were significantly associated with obesity in children and adolescents after controlling for several cofactors. 6 Another study using the NHANES data reported that non-Hispanic white boys were more likely to be overweight/obese, independent of other major risk factors, as a result of exposure to BPA.…”
Section: Metalsmentioning
confidence: 99%
“…144 To support these associations, more research is needed using longitudinal studies to confirm the findings observed in the available cross-sectional studies. 6,[142][143][144] Phthalates are a group of man-made chemicals widely used in industrial and consumer product applications. 8,145,146 Exposure to phthalates can occur from food sources, plastic containers, flooring materials and wall coverings, medical devices, personal care products, lacquers, varnishes, and coatings.…”
Section: Metalsmentioning
confidence: 99%
“…[195][196][197][198][199][200][201][202][203][204][205][206][207][208][209][210] In several, increased urinary BPA concentration was associated with higher odds of increased body mass index, obesity, cardiovascular disease, insulin resistance, and type 2 diabetes (Table S4). Cross-sectional and longitudinal studies have also demonstrated associations between BPA exposure levels and coronary artery disease and peripheral arterial disease.…”
Section: -53mentioning
confidence: 99%
“…Humans are mainly exposed to BPA through food ingestion (Yamada et al 2002 ), and increasing evidence supports its association with impairment of male reproductive function, as well as other health problems and diseases; such diseases include diabetes, obesity, cardiovascular diseases, and cancer (Li et al 2010aSalian et al 2011 ;Batista et al 2012 ;Shankar and Teppala 2012 ;Lee et al 2012 ;Wang et al 2012a ). BPA acts primarily by mimicking the effect of estrogen hormones, modifying DNA methylation, and modulating enzyme activities in utero and in vivo, resulting in metabolic diseases, spermatogenesis defects, and/or infertility in males.…”
Section: Introductionmentioning
confidence: 97%